Mais do que palavras : a associação do abuso emocional na infância com o comportamento suicida - Araújo, Rafael Moreno Ferro de (2015)
Introduction: Adverse childhood experiences are important risk factors for lifetime suicide attempts. However, little is known about the specific contribution of each type of maltreatment on suicidal behavior. The aim of this study was to examine the association between the level of each type of childhood trauma and suicidal behavior severity, controlling for their co-occurrence and common psychiatric disorders. Methods: The data were collected by the Brazilian Internet Study on Temperament and Psychopathology (BRAINSTEP). The final sample consisted of 71429 self-selected volunteers. Childhood maltreatment assessed with the Childhood Trauma Questionnaire (CTQ). Lifetime suicidal behavior was assessed by using the first item of the Suicidal Behavior Questionnaire (SBQ- 17). Results: Controlling for demographic variables, childhood trauma subtypes scores, and psychiatric diagnoses (depression, bipolar disorder, and posttraumatic stress disorder), severe emotional abuse was associated with suicidal ideation and attempts, mainly for serious suicide attempts (OR, 17.76; 95%CI, 14.59-21.62). Emotional abuse had an exponential association with serious suicide attempts, with a peak at the 99th percentile (OR, 53.37; 95%CI, 22.67- 86.58). For other types of trauma, we found positive associations of smaller magnitude: at the 99th percentile for emotional neglect (OR, 1.9; 95%CI, 1.1- 3.0) and sexual abuse (OR, 2.6; 95%CI, 1.9-3.5), and no meaningful trend for physical abuse and physical neglect. Major depressive disorder and emotional abuse had the highest attributable risk fractions, 58% and 56%, respectively. Conclusions: The risk of suicide attempts increased exponentially with higher scores of emotional abuse. Physical maltreatment in childhood was weakly associated with suicidal behavior severity when controlled for emotional trauma. For suicide prevention, mental health public policies should consider including interventions to prevent and treat the consequences of emotional abuse.